1978
DOI: 10.1152/jappl.1978.44.5.782
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tissue volume in dogs during pulmonary edema

Abstract: Pulmonary tissue volume (Vt) and pulmonary capillary blood flow (Qc) were measured in anesthetized dogs by analyzing end-expiratory concentrations of dimethyl ether (DME), acetylene (C2H2), and sulfur hexafluoride during a 30-s rebreathing maneuver. Vt was compared to the postmortem lung weight of control dogs and dogs with hemodynamic and nonhemodynamic (alloxan) pulmonary edema. Qc was compared to the cardiac output measured by dye dilution. A 100-ml increase in alveolar volume (VA) in the range of 1-2 liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 0 publications
4
28
0
Order By: Relevance
“…The combination of these other estimates gives a volume of blood and tissue of about 700 ml for our subjects. The agreement with our estimate is quite close, although the data of Peterson et al (1978) and Petrini et al (1978) (SD 0-42 1). These differences may provide a useful index of inhomogeneity of ventilation or gas "trapping" in subjects with airways obstruction, and the combination of radiographic and gas dilution techniques permits such measurements to be made without a body plethysmograph.…”
Section: Discussionsupporting
confidence: 88%
“…The combination of these other estimates gives a volume of blood and tissue of about 700 ml for our subjects. The agreement with our estimate is quite close, although the data of Peterson et al (1978) and Petrini et al (1978) (SD 0-42 1). These differences may provide a useful index of inhomogeneity of ventilation or gas "trapping" in subjects with airways obstruction, and the combination of radiographic and gas dilution techniques permits such measurements to be made without a body plethysmograph.…”
Section: Discussionsupporting
confidence: 88%
“…In this acute lung injury model, whose collateral ventilation is similar to humans (8), our findings of decreased FRC and underestimation of VTPC at zero end expiratory pressure after induction of lung edema suggests loss of gas exchange units secondary to the oleic acid-induced injury, with inability of the test gas to reach these involved units. Dogs, in which most of the previous studies of the applicability of rebreathing methodology in pulmonary edema have been performed (9,10,16), have a much more developed degree of collateral ventilation. This possibly explains the better correlation of VTPC with gravimetric lung water without the application of PEEP in dogs with lung injury (10,16).…”
Section: Discussionmentioning
confidence: 99%
“…Dogs, in which most of the previous studies of the applicability of rebreathing methodology in pulmonary edema have been performed (9,10,16), have a much more developed degree of collateral ventilation. This possibly explains the better correlation of VTPC with gravimetric lung water without the application of PEEP in dogs with lung injury (10,16). The application of PEEP (up to 10 cm H20) following oleic acid lung injury resulted in a significant increase of FRC indicating lung expansion.…”
Section: Discussionmentioning
confidence: 99%
“…pulmonary capillary blood flow (Qc), re breathing techniques have been developed to calculate these values using rapid-re sponse mass spectrometers. Two different ways of measuring have usually been used: the method called multiple-point zero forcing (MPZF) proposed by Sackner et al [22], and the end-tidal, dead-space cor rection (ETDS) method proposed by Pe terson et al [ 17] and Petrini et al [ 18]. Stud ies carried out to determine the influence of experimental and measurement vari ables [17,18,20,23], correlation with post mortem morphometric studies [4], reprod ucibility of the results [4], and application in lung edema [9,17] have demonstrated that this technique is a useful tool in exper imental work and has possible clinical ap plications.…”
Section: Introductionmentioning
confidence: 99%